Microbial contamination levels in water derived from dental units used in small animal dentistry - Šparaš, Luka; Nemec, Ana; Biasizzo, Majda (Frontiers in Veterinary Science, 2025)
ObjectiveThis prospective study aimed to assess microbial contamination levels in water from dental units used in small animal dentistry.Materials and methodsWater from 24 dental units across various clinics in Slovenia was sampled between July 2022 and September 2024. Samples were tested for Legionella spp., Pseudomonas aeruginosa, Escherichia coli, coliform bacteria, intestinal enterococci, and heterotrophic plate counts (HPC) at 36°C. Statistical analysis assessed associations between the water source, implemented disinfection protocols, and microbial contamination levels of water.ResultsA total of 91.3% of the dental units were microbiologically non-compliant when considering potable drinking water standards. When criteria requiring the absence of Legionella spp., P. aeruginosa, E. coli, coliform bacteria, intestinal enterococci, and HPC < 200 colony-forming units (CFU)/ml were applied, 87.0% of the units were non-compliant. When threshold of HPC < 500 CFU/ml was applied, 79.2% of the units remained microbiologically non-compliant. Distilled water supplied 83.3% of units; the remaining 16.7% used municipal water. Disinfection protocols of dental unit waterlines were implemented in 16.7% of the dental units. None of these parameters were statistically significantly associated with microbial contamination levels of the water derived from dental units.Conclusions and clinical relevanceThe high microbial contamination and limited disinfection use in dental units raise concerns about potential health risks to animals and practitioners. This study highlights the need to establish clear guidelines for microbial levels in water derived from dental units used in small animal dentistry, and to assess disinfection protocols in future research.